PERKEMBANGAN EKOWISATA DI KAWASAN GUNUNG BATUR KECAMATAN KINTAMANI - KABUPATEN BANGLI (STUDI KASUS EKOWISATA DI DESA BATUR TENGAH - KINTAMANI) - I Wayan Darsana (Jurnal Ilmiah Hospitality Management, 2015)
The world tourism has tended to go in the direction natural tourism (Back to Nature) such as Adventure Tourism, Golf, Marine Tourism, Wellness Tourism (Spa) and Ecotourism. One of the special interest tourism that develops today is Ecotourism at central Mount Batur Kintamani District- Bangli. The region has developed well because all parties always support the development and marketing that it makes quite an impact on social life, economy, culture, and environment. The theory used was a theory on destination area lifecycle supported by several concepts such as sustainable tourism and Ecotourism and the data was analyzed qualitatively. The result shows that the local people got involved in the planning, implementation, and management of the ecotourism businesses in which they can derive additional benefit in addition to farming and tilapia fish farming. A tree planting program was also undertaken by non-government organizations. The Department of Forestry has also assigned forest police officers to stand by.